Morphological investigations of fibrogenic action of Estonian oil shale dust. - Küng, V A (1979)
A review of morphological investigations carried out to clarify the pathogenicity of industrial dust produced in the mining and processing of Estonian oil shale is given. Histological examination of lungs of workers in the oil shale industry taken at necropsies showed that the inhalation of oil shale dust over a long period (more than 20 years) may cause the development of occupational pneumoconiotic changes in oil shale miners. The pneumoconiotic process develops slowly and is characterized by changes typical of the interstitial form of pneumoconiotic fibrosis in the lungs. Emphysematous changes and chronic bronchitis also occur. The average chemical content of oil shale as well as of samples of oil shale dust generated during mining and sorting procedures is given. The results of experiments in white rats are presented; these studies also indicate a mild fibrogenic action of Estonian oil shale dust.